HASIL BELAJAR, MINAT DAN KREATIVITAS SISWA SMA PADA PEMBELAJARAN FISIKA MENGGUNAKAN MODEL PROJECT BASED LEARNING DENGAN MEMANFAATKAN BAHAN BEKAS - Qurotul Aini; Albertus Djoko Lesmono; Sri Wahyuni (JURNAL PEMBELAJARAN FISIKA, 2018)
AbstractThe purpose of this research was to examine the effect of the model ofproject based learning by utilizing used materials to the students' learning outcomes,to examine the influence of the model of the project based learning by utilizing theused materials on the interest of learning and to describe the creativity of the studentsin the model of project based learning by utilizing the used materials. The type ofresearch was experiment using posttest-only control group design. The independentvariables in this research was the model of project based learning by utilizing theused materials, the dependent variable in this study is the learning, learning interest,and the students creativity. The result of this research showed that (1) project basedlearning model using the used materials had significant effect on the students'learning outcomes, (2) project based learning model using the used materials hadno significant effect on students' learning interest, (3) Student learning creativityduring use the model of project based learning by utilizing the used materialsincluded in the category quite creative.Key Word: project based learning model, student learning outcame, interests,creativity